Diastolic Heart Failure - Smiseth, Otto A.; Tendera, Michal (Springer London : Imprint: Springer, 2008)
The prevalence of heart failure is increasing and yet a significant proportion of these patients have normal left ventricular (LV) systolic function. In these patients with diastolic dysfunction, heart failure is frequently referred to as diastolic heart failure. While the majority of research into heart failure has concentrated on those patients with LV systolic dysfunction, heart failure patients with preserved systolic function have been grossly underinvestigated. It is critical not only to continue to research and treat those patients with LV systolic dysfunction but also to investigate the possibilities in those patients with diastolic dysfunction with a view to providing tailored management of heart failure for all patients. This book is the first to give a comprehensive overview not only of the diastolic heart failure, but also of different aspects of LV diastolic function in general. It addresses the epidemiology, pathophysiologic mechanisms, diagnostic methods, treatment and prognosis. It also gives an analysis of specific problems, related to coronary artery disease, arterial hypertension, diabetes, hypertrophic and restrictive cardiomyopathies, and constrictive pericarditis. The aim of the Editors and their world-class panel of contributing authors has been not only to summarize the existing knowledge on the role of diastolic dysfunction in heart failure but also to identify the gaps in the understanding of the problem and stimulate discussion in these areas. Consequently, this book will prove useful for both basic scientists and clinicians involved in research and clinical care of patients with heart failure. As such, cardiologists, internists and all disciplines involved in the management of this group of patients will benefit from reading this book.